QIRA'AT AL-QUR'AN IN INDONESIA: APPROACH SOCIO- HISTORICAL ANALYSIS - Romlah Widayati (PT. Jurnal Center Indonesia Publisher, 2025)
This article examines the historical development of qiraat Al-Qur'an in Indonesia using a socio-historical analysis approach. The article discusses the dynamics of the spread and development of qiraat from the time of the arrival of Islam in the 13th century to the contemporary era in 2023. The analysis was carried out based on primary literature studies sourced from classical qiraat books and secondary research documentation from Scopus indexed journals. The research also examines the role of qiraat expert figures in Indonesia as well as the development of qiraat teaching methods that are adapted to the local cultural context. The research results show that the qiraat tradition in Indonesia experienced a significant transformation along with the interaction between Islamic values and local culture, which in turn formed the variety of qiraat that is popular in the archipelago. It is hoped that these findings can fill the gap in literature regarding the history of qiraat in Indonesia and offer a new perspective for the development of religious studies in the future.